ADMINISTRATIVE RESPONSIBILITY FOR NON-FULFILLMENT OF LEGAL REQUIREMENTS OF BODIES AND PERSONS PERFORMING COMPULSORY EXECUTION OF DECISIONS - Vishnyakova, Irina O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: development of scientific and practical background of leading role of the institute of administrative responsibility for not-fulfillment of legal requirements of bodies and persons performing enforced execution of decisions as a guarantee of enforcement proceedings effectiveness. Methods: the general scientific methods of cognition are used in the article - analysis, synthesis, as well as special methods - the axiomatic method and deduction method. Results: This article is devoted to the mechanism of bringing a person to administrative responsibility for failure to comply with legal requirements of bodies and persons enforcing decisions as a tool of ensuring of enforcement proceedings effectiveness. Discussion: the dynamics of legislative framework applied to legal relations being studied was analyzed with a view to compliance with purposes and objectives in this area and reasonability of amendments in future.